Clinical and Bacterial Characteristics of Bloodstream Infections Caused by Listeria monocytogenes in Western China - Nan Wang; Liuqing Yang; Yu Yuan; Chongyang Wu; Chao He (Canadian Journal of Infectious Diseases and Medical Microbiology)
Objective. Bloodstream infections (BSIs) caused by Listeria monocytogenes are linked to high mortality of the patients. Case-specific details related to this disease and causative strains in different districts remain to be characterized. Methods. In this study, medical data of BSIs admitted to West China Hospital from October 2017 to March 2023 were retrieved from the hospital information system. The in vitro antimicrobial susceptibility testing and whole-genome sequencing were performed for L. monocytogenes strains isolated from blood specimens. The genetic relationship of these strains with those in public databases was also analyzed. Result. The in-hospital mortality of L. monocytogenes BSIs was 25.7% (9/35). The changes in consciousness and elevated serum C-reactive protein (CRP) level were found to be the differential factors of L. monocytogenes BSIs (P<0.05). All the 27 strains studied were susceptible to ampicillin, meropenem, and erythromycin. Only 22.2% of them were susceptible to trimethoprim-sulfamethoxazole. The Listeria pathogenicity islands 1 (LIPI-1), truncated LIPI-2, and multiple virulence-related genes outside the LIPIs were determined from these strains. Also, 12 sequence types (STs) and 12 clonal complexes (CCs) were identified and classified into clonal lineages I (9/27, 33.3%) and lineages II (18/27, 66.7%), demonstrating genetic differences with the strains in the database. ST451/CC11 (5/27, 18.5%) and ST8/CC8 (4/27, 14.8%) were the common genotypes. Conclusions. The consciousness change and elevated serum CRP level were found to be the differential factors of L. monocytogenes BSIs. Considering the high virulence of the strains, it is needed to pay more attention to the dissemination of the predominant genotype.